2016
DOI: 10.1016/j.ejps.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin derivatives as novel antihypertensive agents: Synthesis and physiological characterization

Abstract: The antihypertensive flavonol quercetin (Q1) is endowed with a cardioprotective effect against myocardial ischemic damage. Q1 inhibits angiotensin converting enzyme activity, improves vascular relaxation, and decreases oxidative stress and gene expression. However, the clinical application of this flavonol is limited by its poor bioavailability and low stability in aqueous medium. In the aim to overcome these drawbacks and preserve the cardioprotective effects of quercetin, the present study reports on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 28 publications
1
36
0
2
Order By: Relevance
“…Another study also verified in rat heart that application of quercetin resulted in positive inotropic and lusitropic effects at very low concentrations (10 À10 to 10 À8 M) and negative inotropic and lusitropic effects at higher concentrations (10 À7 and 10 À6 M) [22]. In the heart, activation of a1-adrenoceptor elicits positive inotropic response by activating the GTP-binding protein (Gq) that activates phospholipase C and increases signalling through IP 3 /Ca 2+ /PKC cascade [23].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Another study also verified in rat heart that application of quercetin resulted in positive inotropic and lusitropic effects at very low concentrations (10 À10 to 10 À8 M) and negative inotropic and lusitropic effects at higher concentrations (10 À7 and 10 À6 M) [22]. In the heart, activation of a1-adrenoceptor elicits positive inotropic response by activating the GTP-binding protein (Gq) that activates phospholipase C and increases signalling through IP 3 /Ca 2+ /PKC cascade [23].…”
Section: Discussionmentioning
confidence: 73%
“…It was observed that quercetin‐elicited positive inotropism and lusitropism was dependent on β 1 /β 2 ‐adrenoceptors and was associated with increased intracellular cAMP, while the negative inotropism and lusitropism observed at higher concentrations were dependent on α‐adrenoceptor activation . Another study also verified in rat heart that application of quercetin resulted in positive inotropic and lusitropic effects at very low concentrations (10 −10 to 10 −8 M) and negative inotropic and lusitropic effects at higher concentrations (10 −7 and 10 −6 M) . In the heart, activation of α1‐adrenoceptor elicits positive inotropic response by activating the GTP‐binding protein (Gq) that activates phospholipase C and increases signalling through IP 3 /Ca 2+ /PKC cascade .…”
Section: Discussionmentioning
confidence: 83%
“…Methyl- and hyro-sliybin derivatives have been reported to be 10-fold more potent than the parent compound, sylibin [202205]. The introduction of hydrophobic functional groups (e.g., ethyl substitution) on the hydroxyl (OH) groups in quercetin significantly enhances its stability by preventing oxidative degradation of the hydroxyl groups [206]. Furthermore, the hydrophobic substitutions increase lipophilicity (quercetin’s clogP = 2, hydrophobic derivatives clogP = 3–12), which increases penetrability through biological membranes (bioavailability was increased from 10.7% for quercetin to 18.8% for one of its derivatives) [206].…”
Section: Approaches To Surmount Flavonoid Pk/pd and Other Barriersmentioning
confidence: 99%
“…The introduction of hydrophobic functional groups (e.g., ethyl substitution) on the hydroxyl (OH) groups in quercetin significantly enhances its stability by preventing oxidative degradation of the hydroxyl groups [206]. Furthermore, the hydrophobic substitutions increase lipophilicity (quercetin’s clogP = 2, hydrophobic derivatives clogP = 3–12), which increases penetrability through biological membranes (bioavailability was increased from 10.7% for quercetin to 18.8% for one of its derivatives) [206]. It has also been shown that blocking some groups (e.g., C3 hydroxyl and C7 hydroxyl groups) in quercetin by the introduction of the lipophilic moiety pivaloxymethyl (POM) enhances its solubility, decreases its metabolism, enhances stability (half-life increased from 10 h for quercetin to >72 h for its quercetin-POM conjugates at pH 7.4), and increases its effectiveness by preventing chemical and metabolic hydrolysis [207].…”
Section: Approaches To Surmount Flavonoid Pk/pd and Other Barriersmentioning
confidence: 99%
“…The in vitro bioavailability study was carried out in a simulated gastric and intestinal environment through the previously reported method of the dialysis tubing procedure (Grande et al, 2016). The experiment is based on two successive enzymatic phases: pepsin and pancreatin digestions, which occurs in the first 2 h and in the following 4 h, respectively.…”
Section: In Vitro Bioavailability Studiesmentioning
confidence: 99%